Explaining Inequality and Poverty Reduction in Bolivia - Vargas, Mauricio (IMF Working Papers; Working Paper ;, 2015)
We investigate the factors driving Bolivia's success in reducing inequality and poverty during the last 15 years. Our evidence suggests that the reduction was driven mainly by labor income growth at the bottom end of the income distribution. Increases in non-labor income (rents, transfers, remittances) also played a role, but a smaller one, although the introduction of Renta Dignidad has made a big difference for the elderly poor. Labor income increases were concentrated in the informal, low-skilled service and manufacturing sectors. As the gains from the commodity boom go into reverse, and the fiscal envelope becomes much tighter, it will be essential that labor and social policies are well designed and targeted to preserve the poverty and inequality reduction of the last 15 years.